Resíduos de cama de frango para fabricação de biochar - Pereira, Moisés Edevaldo (Universidade Federal de São Carlos, 2019)
Brazil has a large generation of poultry litter, as a result of its worldwide prominence in the production of broiler chicken. The poultry litter biomass generates considerable environmental impacts according to its volume produced. Thus, the general objective of this work was to characterize the poultry litter biomass to verify the possibility of using as a raw material for biochar manufacture. To characterize the poultry litter, was analyzed samples of sawdust pine, poultry litter with 1 and 2 lots of broiler chicken. Were performed immediate analyze, moisture, thermogravimetric analysis (TGA), scanning electron microscopy (MEV), dispersive energy spectroscopy (EDS) and macro and micronutrient analysis were performed only with poultry litter with 1 and 2 lots of broiler chicken (chapter 2). For the manufacture of biochar, were used 5 treatments with the following residence times: 0.5, 1, 2, 4 and 6 hours. The biochar produced were subjected to immediate analysis, moisture, gravimetric yield, scanning electron microscopy (MEV), dispersive energy spectroscopy (EDS) and higher heating value (HHV), shown in chapter 3. The results showed that poultry litter biomass has great potential for biochar manufacture, with expressive values of phosphorus, potassium, calcium and others, and pH of 8.4, important characteristics for biochar with soil use. The results showed that the best conditions for biochar manufacture are with pyrolysis temperature of 450 °C and residence time of 0.5 hour, with high gravimetric yield of 37.21%. The studies also concluded that use of both biomass and biochar are not indicated for use in energy due to characteristics such as moisture, ash content and higher heating value.
Poultry litter waste for biochar manufacturing
Keywords: Cama de aviário.; Pirólise.; Biomassa.; Recuperação de solo.; Poultry litter.; Pyrolysis.; Biomass.; Soil recovery.; CIENCIAS EXATAS E DA TERRA